Towards a social theoretical foundation for Information Science - Martínez-Ávila, Daniel (Anuario ThinkEPI, 2018)
The scientific nature of Information Science and its interdisciplinary relationships with other fields are discussed. I review some of the theoretical positions that coexist, oftentimes in conflict with each other, including the Mathematical Theory of Communication, Social Epistemology, Floridi´s Philosophy of Information, and theoretical positions in areas such as information technologies, information retrieval, bibliometrics, and big data. I conclude that the theoretical project of Social Epistemology, in its original conception by Egan and Shera, in its current manifestations in the philosophy of Steve Fuller, and in the paradigm of domain analysis by Hjí¸rland, is one of the most solid proposals for providing a social, theoretical foundation for Information Science.
Keywords: Information Science; Interdisciplinarity; Theory; Social Epistemology; Philosophy of Information; Big data.